Changes in serum Interleukin-33 concentration before and after treatment with pegylated interferon alfa-2a plus ribavirin in patients with chronic hepatitis C genotype 1b infection - Cacopardo, Bruno (Kowsar, 2012)
BACKGROUND: IL-33 is a novel member of the IL-1 family, which has been shown to play an important role in T helper 2 (Th2)-associated immune responses. Recent studies have suggested a possible role for IL-33 in the pathogenesis of liver damage during acute and chronic hepatitis; furthermore, IL-33 may be involved in the development and progression of liver fibrosis. OBJECTIVES: To evaluate serum IL-33 levels in a group of patients with chronic hepatitis C (CHC) genotype 1b at enrolment and after a course of pegylated (PEG)-IFN plus ribavirin. PATIENTS AND METHODS: 60 patients with chronic hepatitis C (CHC) and 65 healthy controls were examined and compared for serum IL-33 levels by ELISA. All CHC patients were submitted to liver biopsy either before starting antiviral treatment or during post-treatment follow up. We evaluated whether post-treatment IL-33 concentration was associated with histologic outcome as well as with virologic response to therapy. RESULTS: Serum IL-33 levels were significantly higher among CHC patients in comparison with healthy controls. IL-33 concentration was lower among patients with a METAVIR fibrosis score F1-F2, compared with those having a more advanced liver disease (METAVIR stage F3-F4). In addition, sustained virologic response (SVR) was associated with a significant drop in IL-33 levels, whereas no changes were found among relapsers and nonresponders. Analogously, patients experiencing liver histologic improvement after antiviral therapy had lower post-treatment IL-33 levels in comparison with baseline values. Contrarily, no variations were detected among subjects with worsened or stable histologic features. CONCLUSIONS: IL-33 may represent a new and easy-to-detect biomarker for the diagnosis of liver damage in CHC patients, as it appears to be modulated in parallel with biochemical and histologic parameters, such as ALT levels and liver fibrosis. Furthermore, considering that serum IL-33 concentration was significantly reduced following a successful course of antiviral treatment, this cytokine may also represent a sensitive indicator of SVR.